Experience from a single paediatric transplant centre with identification of some protective and risk factors concerning the development of hepatic veno-occlusive disease in children after allogeneic hematopoietic stem cell transplant. - Maximova, N; Ferrara, G; Minute, M; Pizzol, A; Kiren, V; Montico, M; Gregori, M; Tamaro, P (Int J Hematol, 2014)
Hepatic veno-occlusive disease (VOD) is a frequent and severe complication of hematopoietic stem cell transplantation (HSCT) affecting 9.6-17.3 % of cases. 200 HSCT, performed between January 1995 and March 2013 in our Paediatric HSCT Centre in Trieste, were retrospectively analysed to evaluate the frequency of VOD and to identify the associated risk factors. The frequency of VOD according to the Seattle criteria was 17 %, within the range reported in literature. The mortality rate was 37.5 % (75 out of 200 transplantations) in the general population and 73.5 % (25 out of 34) in VOD patients (p < 0.05). Veno-occlusive disease significantly decreased from 38 % (1995-2000) to 8 % (2007-2013) p < 0.05. Univariate and multivariate analyses identified sepsis and pre-transplant ferritin levels above 1000 ng/ml as two significant risk factors for VOD, while the use of tacrolimus appeared to be associated with a lower VOD risk. Veno-occlusive disease still remains an important cause of transplant-related mortality even if it appears to have decreased over the last few years.
Keywords: Adolescent; Child; Child, Preschool; Female; Hematopoietic Stem Cell Transplantation; Hepatic Veno-Occlusive Disease; Humans; Infant; Infant, Newborn; Male; Mortality; Retrospective Studies; Risk Factors; Transplantation, Homologous; Young Adult